Shear Performance of Concrete Beams with a Maximum Size of Recycled Concrete Aggregate - Brian Jacks Odero; Raphael N. Mutuku; Timothy Nyomboi; Zachary Abiero Gariy (Advances in Materials Science and Engineering)
The use of concrete mixes with recycled materials has gained traction in research communities. However, the major drawback of the recycled concrete aggregate (RCA) has been the contribution of the cement paste mortar attached to the surface. The quantity of surface-attached mortar on the virgin aggregate dominates and defines the shear performance of concrete beams. Concrete shear failure is usually abrupt and catastrophic, especially in concrete beams without shear reinforcement. The effectiveness of the maximum size of RCA for the performance of untreated and treated with pozzolanic cement and rice husk ash (RHA) slurry was investigated. A total of sixteen (16) beams containing RCA of four (4) maximum sizes, 10, 14, 20, and 25 mm, were prepared and tested after 28 days. The beams were loaded in shear using shear span-depth ratios of 1.25 and 2.50. The results showed that the shear strength of the beams increases as the aggregate size increases to a maximum size of 20 mm, beyond which the shear strength reduces. It was attributed to the attached mortar, which increased as the size of the aggregate increased, creating a weak zone for shear failure in the concrete. In addition, RCA pretreatment using slurry-containing cement and RHA strengthened the attached mortar on the aggregate surface. It resulted in a dense and more compact aggregate that slightly improved the shear strength by about 2.2% for beams containing 20 mm RCA size. The ultimate shear strength of the experimental work in the study was predicted using eight (8) selected models from the literature. Models that account for the aggregate size and shear span to depth ratio resulted in shear strength ratios of 1.29, 0.91, 1.08, and 1.20 for Bažant and Becq-Giraudon, 2002, Zsutty, 1968, Xu et al., 2012, and Gastebled and May, 2001, which are almost similar outcomes to the experimental results.